Formation of unsaturated hydrocarbons, carbonyl compounds and PAHs in a non-premixed methane/air flame doped with methyl butanoate: CFD modeling and comparison with experimental data. (15th October 2016) - Lin, Kuang C.; Chiu, Chuang-Te; Tao, Hairong; Liao, Yu-Chen
Abstract: The study proposes a base kinetic model of biodiesel fuels to distinguish mass-spectrometrically measured hydrocarbons, carbonyl compounds and light-weight polycyclic aromatic hydrocarbons (PAHs) in a methane/air non-premixed flame doped with methyl butanoate (MB). The computational procedure starts with reducing a detailed MB mechanism to generate a minimized but reasonably accurate skeletal mechanism which is then used to combine with previously published submodels that describe PAHs and related compounds. The newly derived MB-PAH mechanism with 83 species and 520 reactions is systematically validated against results of existing detailed and skeletal MB mechanisms. Without empirical adjustment of rate constants in elementary reactions, the MB-PAH mechanism incorporated into a 2-D axisymmetric laminar finite-rate model, for the first time, is able to predict experimentally measured centerline mole fractions of 14 intermediates. The computationally identified intermediates are in accordance with the mass-spectrometric determinations, where the species include propyne/propadiene (C3 H4 ), propene (C3 H6 ), vinylacetylene (C4 H4 ), but-1-ene/but-2-ene (C4 H8 ), ketenes (CH3 CHCO and C2 H5 CHCO), prop-2-enal (C2 H3 CHO), 1, 3, 5-Hexatriyne (C6 H2 ), benzene (C6 H6 ), naphthalene (C10 H8 ), phenanthrene (C14 H10 ) and pyrene (C16 H10 ). Moreover, the reaction pathway analysis reveals the correlation between the decomposition of MB and formation of the investigated intermediates.